Relationship of work-family conflict with burnout and marital satisfaction: cross-domain or source attribution relations? - Razieh Bagherzadeh; Ziba Taghizadeh; Eesa Mohammadi; Anoshirvan Kazemnejad; Abolghasem Pourreza; Abbas Ebadi (Tabriz University of Medical Sciences, 2016)
Background: The present study was conducted to examine the relationship between two dimensions of work-family conflict (WFC) with marital satisfaction and burnout in a society in which few studies have been done about the consequences of WFC. Methods: A cross-sectional study was conducted in 2015. Surveys were distributed to 420 employed married women with various jobs living in Bushehr province, Iran. Data were collected using a questionnaire for demographic characteristic, the Netmeyer's WFC questionnaire, Maslach Burnout Inventory: General Survey (MBI-GS), and Enrich maritalsatisfaction questionnaire. The data were analyzed using descriptive and inferential statistics. Results: There was a negatively significant association between work interference with family(WIF) and overall burnout as well as emotional exhaustion (P < .01). Family interference with work (FIW) was significantly associated with depersonalization (P < .01). The overall marital satisfaction and its sub-scales were significantly associated with WIF (P < .01) and FIW (P < .01 for overall marital satisfaction and P < .05 for its sub-scales). Conclusion: In terms of practical implication, to avoid creating disadvantages of WIF and FIW,facilitation in two domains of improving work and family conditions can be a useful means to prevent WFC and its consequences.